Pengaruh Relationship Marketing Terhadap Loyalitas Pelanggan Pengguna Kartu Prabayar Telkomsel di Kota Mataram - Asdianti, Vivi; Ika Supryadi, Didy (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to determine the influence of trust, commitment, communication, and problem handling on customer loyalty of Telkomsel prepaid card users in Mataram City. This type of research is an associative research that has the purpose of finding out the influence or relationship between two or more variables. The data collection method is carried out through the distribution of questionnaires to customers who have used a product offered by Telkomsel in Mataram City. The sample used in this study was 150 samples with a non-probability sampling technique using the purposive sampling method. The technique in data processing uses the multiple linear regression analysis method with the help of the IBM SPSS 24 sofiwere application. The results of this study show that the variables of trust, commitment, communication, and problem handling partially have a positive and significant effect on customer loyalty in Mataram City.